The Influence of Leadership, Work Culture, Motivation and Technology Acceptance on Employee Performance Moderated by the Work Environment at the Secretariat General of the Ministry of Finance - Alek Sudarso; Zahara Tussoleha Rony; Faroman Syarief (Dinasti Publisher, 2023)
This study aims to examine the influence of leadership, work culture, motivation and technology acceptance on employee performance moderated by the work environment. The method used in this study is a quantitative method using a causal study survey approach. This research was conducted at the Secretariat General of the Ministry of Finance with a total sample of 250 employees from a population of 2,740 employees. The data analysis technique in this study used the Structural Equation Modeling - Partial Least Square (SEM-PLS) method with the help of the SMART PLS Application to conduct research data analysis. In this study, instrument testing was carried out by conducting validity tests, reliability tests, outer models, inner models and hypothesis testing.